2015
DOI: 10.4161/15548627.2014.981915
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage contributes toPseudomonas aeruginosaactivation of the inflammasome and is downregulated by autophagy

Abstract: Abbreviations: Three-MA, 3-methyladenine; AIM2, absent in melanoma 2; ATG, autophagy related; ATPIF1, ATPase inhibitory factor 1; BID, BH3 interacting domain death agonist; BMDM, bone marrow-derived macrophages; BrdU, 5-bromo-2-deoxyuridine; CASP, caspase; GFP, green fluorescent protein; IL1B, interleukin 1, b; LC3B, microtubule-associated protein 1 light chain 3 b; LDH, lactate dehydrogenase; LPS, lipopolysaccharide; Mito-TEMPO, (2-(2, 2, 6, 6-tetramethylpiperidin-1-oxyl-4-ylamino)-2-oxoethyl)triphenylphospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 42 publications
5
112
0
Order By: Relevance
“…Overexpression of the NLRP3 inflammasome core molecules or treatment with IL-1␀ promoted autophagy in P. aeruginosa-infected macrophages, which is consistent with the findings of others showing that caspase1 increases the autophagic influx by upregulating Beclin1 expression (43). Jabir et al demonstrated that the DNA released from damaged mitochondria contributes to P. aeruginosa-mediated activation of the IPAF inflammasome and is downregulated by autophagy (31). These findings indicate the cross talk between inflammasome and autophagy.…”
Section: Figsupporting
confidence: 78%
“…Overexpression of the NLRP3 inflammasome core molecules or treatment with IL-1␀ promoted autophagy in P. aeruginosa-infected macrophages, which is consistent with the findings of others showing that caspase1 increases the autophagic influx by upregulating Beclin1 expression (43). Jabir et al demonstrated that the DNA released from damaged mitochondria contributes to P. aeruginosa-mediated activation of the IPAF inflammasome and is downregulated by autophagy (31). These findings indicate the cross talk between inflammasome and autophagy.…”
Section: Figsupporting
confidence: 78%
“…It is well known that mitochondria play a key role in the activation of the NLRP3 inflammasome [22][23][24]. Our work revealed that the decreased activity of mitochondrial respiratory chain complex I caused by ATP was restored by levornidazole (Fig.…”
Section: Levornidazole Suppresses the Nlrp3 Inflammasome By Protectinsupporting
confidence: 46%
“…adaptor, thus limiting TRIF signaling, could be a possible explanation (Jabir et al, 2014). Indeed, TRIF signaling was required not only to eventually restrain the inflammatory response in VVC but also to sustain IL-1Ra production in infection (unpublished data).…”
Section: Discussionmentioning
confidence: 94%